2014
DOI: 10.1111/sjoe.12075
|View full text |Cite
|
Sign up to set email alerts
|

Do Surveillance Cameras Affect Unruly Behavior? A Close Look at Grandstands

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 16 publications
0
27
0
3
Order By: Relevance
“…The studies cover a breadth of strategies and interventions to counter antisocial and violent behaviour The few quasi-experimental designs varied in both design and quality; there were only four studies that were assessed as at least 3 on the adjusted Maryland Scientific Methods Scale and provide credible evidence of effectiveness (Di Domizio and Caruso, 2015;Giacomantonio et al 2015;Priks 2014;Schaap et al 2015).…”
Section: The Quality and Quantity Of Identified Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…The studies cover a breadth of strategies and interventions to counter antisocial and violent behaviour The few quasi-experimental designs varied in both design and quality; there were only four studies that were assessed as at least 3 on the adjusted Maryland Scientific Methods Scale and provide credible evidence of effectiveness (Di Domizio and Caruso, 2015;Giacomantonio et al 2015;Priks 2014;Schaap et al 2015).…”
Section: The Quality and Quantity Of Identified Evidencementioning
confidence: 99%
“…A study by Priks (2014) evaluated the effect of surveillance cameras installed in Swedish football stadiums on unruly behaviour. The author took advantage of a decision in 2000 by the Swedish Football Association that all stadiums hosting matches in Allsvenskan (the highest Swedish league) needed to be equipped with cameras within two years.…”
Section: What Is the Intervention And Where Has It Been Used?mentioning
confidence: 99%
“…The paper also contributes additional evidence of the effectiveness of monitoring to an emerging literature on the role of CCTV cameras in combating crime (Priks 2014(Priks , 2015King, Mulligan, and Raphael 2008;Farringdon 2009, 2003).…”
mentioning
confidence: 99%
“…5 The effectiveness of CCTV cameras in reducing crime is a current topic, with million dollars being spent in this public safety infrastructure. Priks (2014Priks ( , 2015 document the causal effects of CCTV cameras on unruly behavior and some types of crime, using temporal variation in CCTV installation in Swedish stadiums and underground. King, Mulligan, and Raphael (2008) showed that property crime was reduced as a result of CCTV monitoring on the streets of San Francisco.…”
mentioning
confidence: 99%
“…The reasoning behind this is that surveillance cameras may both prevent crime by signalling that one is being watched, as well as increasing the likelihood that one is caught in case of law‐breaking behaviour. Several studies (e.g., Poyner, ; Priks, ) do indeed suggest that the presence of cameras decreases undesired behaviour. We expect camera surveillance to be especially effective when a rational process of cost‐benefit estimation is involved, linking back to the rational choice perspective (Cornish & Clarke, ).…”
Section: Introductionmentioning
confidence: 99%